ADCY3, neuronal primary cilia and obesity. (February 2018) - Barroso, Inês
Two new studies identify rare homozygous variants inADCY3 that are causal for monogenic obesity in consanguineous families of Pakistani origin and are associated with increased risk of obesity in Greenlandic individuals. Greenlandic carriers of homozygous loss-of-function variants inADCY3, and individuals from trans-ancestry studies with a burden of rareADCY3 loss-of-function variants, also have increased risk of type 2 diabetes.